Rancang Bangun Sistem Monitoring Hasil Energi Listrik pada Prototipe Turbin Darrieus untuk Optimalisasi Energi Berbasis Iot - Syah Reza Hasyim; Agus Dwi Santosa; Faris Nofandi (International Forum of Researchers and Lecturers, 2025)
This research aims to design and build an Internet of Things (IoT)-based electrical energy monitoring system on a Darrieus turbine prototype to optimize energy yield. This research using the Research and Development or RnD method, this method was chosen by researchers because it can provide solutions, enable the development and application of more effective learning methods. The system uses NodeMCU ESP32 sensors to measure important parameters such as voltage, current, power, and energy produced by the turbine. The collected data is then analyzed and visualized through IoT platforms such as ThingsBoard, which allows real- time monitoring of the turbine's performance. The integration of IoT in this system is expected to improve energy use efficiency by providing useful information for management and decision-making in turbine operations. This research also fills the gap in Darrieus turbine development with an approach that combines IoT-based monitoring and energy yield optimization, and can be applied to improve the efficiency of renewable energy in Indonesia